The Mediating Role of Work Engagement in the Relationship Between Organizational Culture and Employee Performance in Indonesian MSMEs - Supiah Ningsih; Danil Syahputra; Rudy Irwansyah (Journal of Economics, Entrepreneurship, Management Business and Accounting, 2026)
Purpose - This study aims to examine the mediating role of work engagement in the relationship between organizational culture and employee performance in Indonesian Micro, Small, and Medium Enterprises (MSMEs). Design/Methodology/Approach – A quantitative cross-sectional survey design was employed. Data were collected from 210 MSME employees across trade, service, and manufacturing sectors in North Sumatra, Indonesia. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to assess direct and indirect relationships among organizational culture, work engagement, and employee performance. Findings – The results indicate that organizational culture has a positive and significant effect on employee performance (β = 0.381, p < 0.001) and work engagement (β = 0.721, p < 0.001). Work engagement also significantly affects employee performance (β = 0.409, p < 0.001) and partially mediates the relationship between organizational culture and employee performance (β = 0.295, p < 0.001). The model demonstrates substantial explanatory power, with R² values of 0.520 for work engagement and 0.612 for employee performance. Research Limitations/Implications – This study is limited by its cross-sectional design, which restricts causal inference, and its focus on MSMEs in North Sumatra, which may limit generalizability. Future research is encouraged to adopt longitudinal designs and broader regional samples. Practical Implications – The findings highlight the importance of fostering a supportive organizational culture to enhance employee engagement and improve performance outcomes in MSMEs. Originality/Value – This study contributes to the literature by providing empirical evidence on the mediating role of work engagement in MSMEs, a context that remains underexplored in prior research.